European governance and supranational institutions : making states comply - Tallberg, Jonas (London ; New York : Routledge, 2003)
Examines the influence of the European Commission and the European Court of Justice in the political and legal enforcement of member state compliance in the EU.
1. Introduction -- 2. Principals, supervisors, and agents in EU enforcement -- 3. The European market and state non-compliance -- 4. Centralized enforcement through supranational institutions : the exploitation of existing powers -- 5. Delegation of enforcement powers : the supranational quest for sanctioning authority -- 6. Decentralized enforcement through national courts : the supranational creation of new powers -- 7. Conclusion.
Includes bibliographical references (pages 152-171) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Law -- European Union countries; Sanctions (Law) -- European Union countries; Law enforcement -- European Union countries; Europe -- Economic integration; Sanctions (Droit) -- Pays de l'Union européenne.; Lois -- Application -- Pays de l'Union européenne.; Europe -- Intégration économique.; LAW -- International; International economic integration; Law; Law enforcement; Sanctions (Law); Europe; European Union countries; Rechtshandhaving; Rechtbanken; Europese Unie; Europees recht; Nationaal recht; EU-landen.; Lagstiftning -- EU-länderna.